Reação de cultivares e danos causados por Meloidogyne javanica e Meloidogyne enterolobii em abacaxizeiros - Pereira, Amilton José (2011)
It was evaluated the reaction of four pineapple cultivars (Vitória, Smooth Cayenne, Pérola, and MD-2 (Gold)) and damages caused by M. javanica and M. enterolobii in a greenhouse at CCA-UFES, in the city of Alegre, ES. Sixty days after the plantation, plan